Employment Adjustment over the Business Cycle: The Impact of Competition in the Labor Market - Douglas A. Webber (Institute of Labor Economics (IZA), 2018)
Using linked employer-employee data which covers the majority of U.S. employment, I examine how frictions in the labor market have evolved over time. I estimate that the labor supply elasticity to the firm declined by approximately 0.19 log points (1.20 to 1.01) since the late 1990's, with the steepest declines occurring during the financial crisis. I find that this decline in labor market competition cost workers about 4 percent in lost earnings. I also find evidence that relatively monopsonistic firms smooth their employment behavior, growing at a rate lower than relatively competitive firms in good economic climates and slightly higher during poor economic climates. This conforms with the predictions of recent macroeconomic search models which suggest that frictions in the economy may actually reduce employment fluctuations.
Keywords: J21; J42; J64; 330; monopsony; Great Recession; adjustment costs